A testbed for optimal coating selection for micromilling of biomedical grade TI-6AL-4V. - Hawi, Sara (Cranfield University, 2019)
One of the biggest challenges in precision micro-machining of titanium alloys is the tool wear as titanium is characterised as a “difficult to cut” material. Tool coatings provide a promising solution for the problem of tool wear while offering a low cost high value machining route. This project aims to explore the design of engineering material systems along with machining parameters to guide the choice of tool coating while machining biomedical grade Ti-6Al-4V. The overarching aim is to identify a low cost tooling such as WC coated with the right coating composition together with the appropriate machining parameters. The research methodology applied to work towards this aim employs a design of experimental approach using the Taguchi method such that the spindle speed, feed rate and coating would be varied. Both qualitative and quantitative analysis of the machining process was carried out to qualify the machining performance. During the machining trials, data was gathered and analysed to study the effect of cutting parameters on the specific cutting energy, material removal rate and surface roughness.
Keywords: titanium alloys; micro-machining; precision; engineering material; coating composition; parameters